ALIH KODE DAN CAMPUR KODE TOKOH DALAM FILM RUDY HABIBIE SEBAGAI PEMBELAJARAN BERBASIS TEKS - Nurfitri, Desti; Saman, Sisilya; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe researcher selected code and mixed switching as the research focus because of a frequet phenomenon in daily lives. Movie was selected because of portrayal of lives which was depicted into scenes in certain topic. The problems discussed in this research were code switching, mixed switching, factors that cause the used of code and mixed switching in movie Rudy Habibie and forms of texts as supplementary materials in teaching indonesian language, with a purpose to describe the problems. This research used some methods, namely data collection method, data validity assessment and data analysis. These methods aimed to give depiction of the result of research systematically, factually and acurately regarding facts, characters and the relations of problems investigated. This research was qualitative by using scientific background. The corpus was trascripted dilagoues of movie Rudy Habibie and the data used was utterances which contain code and mixed switching. The data collection technique consisted of data transcript techniue and note technique. Data validity assessment technique was observation and adequate reference. The results of code and mixed switching of movie Rudy Habibie were: code switching was internal and external code switching, while mixed switching wasin a form of words and phrases.Â Keywords: Code Switching, Characteristics, Mixed Switching